"Occupational sitting kills; but who cares?": Quantitative analysis of barriers and facilitators of sedentary behavior in Indian white-collar workers. Issue 2 (7th February 2022) - Shaikh, Alfiya; Mohapatra, Sidhiprada; Chandrasekaran, Baskaran
Abstract: The knowledge, attitude and practices of employees and employers toward reducing sedentary behavior (SB) and improving physical activity (PA) at Indian workplaces remain unclear. A bespoke questionnaire assessing barriers and facilitators of occupational SB and PA practices as informed by the theoretical framework and behavioral change wheel model was adapted. Two hundred and three white-collar workers (both employees and managers) from eight corporate sectors were inquired about the SB, and PA practices at workplaces. The dichotomous variables of barriers and facilitators were analyzed by nonparametric tests. Excessive sitters had good knowledge (>75%), good attitude (>85%) but poor workplace SB and PA practice (>90%). Workplace SB, or PA practices differed between employers and employees. Low practice of workplace PA or SB interventions may be due to lack of workplace policies for SB interventions.